25 anos do PPGE (25 years of PPGE) - Saviani, Dermeval (Revista Eletrônica de Educação, 2017)
In this conference, which took place at UFSCar (Brazil) in 2001, the author addresses the first period of existence of the PPGE / UFSCar, that is, its creation (1974-76), through an agreement with the Carlos Chagas Foundation and its first crisis (1977-78). He reports on his experience as first coordinator and highlights the innovative aspects that characterized the initial project, such as its curricular structure, the objectives of the concentration areas and the agreement itself with the Carlos Chagas Foundation. Keywords: Universidade Federal de São Carlos, Postgraduate Program in Education, Fundação Carlos Chagas. Nesta conferência, proferida no PPGE/UFSCar (Brasil), em 2001, o autor aborda o primeiro período de existência do Programa, isto é, a sua criação (1974-76), por meio de um convênio com a Fundação Carlos Chagas e a sua primeira crise (1977-78). Relata a sua experiência como primeiro coordenador do PPGE e destaca os aspectos inovadores que caracterizaram o projeto inicial, como a sua estrutura curricular, os objetivos das áreas de concentração e o próprio convênio com a Fundação Carlos Chagas. Palavras-chave: PPGE/UFSCar, Pós-Graduação em Educação, Fundação Carlos Chagas.